2018
DOI: 10.1371/journal.pone.0203454
|View full text |Cite
|
Sign up to set email alerts
|

Why is the inpatient cost of dying increasing in India?

Abstract: IntroductionThere is an evidence of increasing inpatient expenditure for decedents. Estimates used to assess the economic burden of out-of-pocket (OOP) healthcare expenditure provide an underestimation for inpatient decedent cases. The aims of this paper are to study the trend and pattern of inpatient decedent expenditure and decipher the reasons behind the increasing cost in India.MethodsUsing three rounds of national level National Sample Survey (NSS) data on morbidity & healthcare conducted during 1995–2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…age, SES, inpatient death) that have been studied elsewhere, our results have corroborated well with those studies. For example, our observation of less costly and less intensive care in the oldest age groups [4649], association between lower SES with increased frequency of inpatient visits [5356], and excessive inpatient expenditure from decedents [67] have also been reported in other studies. These give us confidence that the novel results in our studies could apply to those populations and countries as well.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…age, SES, inpatient death) that have been studied elsewhere, our results have corroborated well with those studies. For example, our observation of less costly and less intensive care in the oldest age groups [4649], association between lower SES with increased frequency of inpatient visits [5356], and excessive inpatient expenditure from decedents [67] have also been reported in other studies. These give us confidence that the novel results in our studies could apply to those populations and countries as well.…”
Section: Discussionsupporting
confidence: 68%
“…Expenditure of visit which ended in death accounted for almost half of total observed expenditure of a patient on average. Although analysis was performed at patient-level, a study in India found that 2014 to 2015 inpatient expenditure for decedents was 64% higher than non-decedent [67]. This observation may be due to more intensive care rendered at the end-of-life (EOL), prior to the patient passing on in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The study, using the NSS data set of the 60th round (2004)(2005), finds that the cost is significantly higher for the group, who are rural residents, suffering from chronic ailments, staying in hospitals for longer duration, and utilizing private healthcare facilities. Another study by Das and Ladusingh 13 further confirms from the NSS dataset for the period 1995 to 2015 that while mean decedent inpatient expenditure doubled during 2004-2005 to 2014-2015, diagnostic and bed charges increased manifolds. Controlling all other potential factors, the inpatient expenditure among elderly decedents increased substantially between 1995-1996 and 2014-2015.…”
Section: Introductionmentioning
confidence: 82%
“…The out-of-pocket expenses on in-patient decedents were found to be unbearable for the majority of families in the large National Sample Survey. 4 The costs of ICU care were not explored further in this study.…”
mentioning
confidence: 99%